Comparative evaluation of localized genotoxicity between the field of focus and scatter following exposure to cone beam computed tomography using buccal mucosal micronuclei assay: A cross-sectional study - Rajeswari Sreeenivas; Algi Nadil; Priya Thomas; Giju George Baby; Deepu George Mathew; Pooja Latti; Jiss George (Journal of Orofacial Sciences)
Introduction: X-rays, a crucial diagnostic tool, are known for their cytotoxic and mutagenic effects, capable of inducing gene mutations and chromosomal aberrations. Despite this, the risks, especially from dental X-ray machines, are often overlooked. Digital X-ray imaging, particularly cone-beam computed tomography (CBCT), is now common in dental practice due to its reduced radiation dose, high accuracy, and rapid scanning. However, no radiation dose is entirely safe, and biological effects accumulate over time. A significant drawback of CBCT is its emission of scattered X-rays. Biomonitoring studies, such as the micronucleus (MN) assay on buccal mucosal cells, are essential for evaluating genotoxic risk from diagnostic radiation. To evaluate and compare the genotoxic and cytotoxic damage in exfoliated cells, using the buccal cytome assay following exposure to x-ray radiation during partial CBCT exposure between the field of direct and scatter radiation. Materials and methods: To establish the genotoxic and cytotoxic impacts of CBCT radiation on the mucosa and its effects on the basal cell layer of the epithelium, the research enlisted 35 subjects aged 18 to 60 years. Before and after CBCT exposure, samples of exfoliated oral mucosa were stained with Feulgen. Nuclear anomalies were then graded using image analysis software, and 500 intact exfoliated epithelial cells were checked for micronuclei and other nuclear anomalies according to 1992 criteria set by Tolbert et al. Result: The results showed that cytotoxic anomalies, such as karyorrhexis and karyolysis, were significant with a P-value of <0.01, while all other anomalies, including micronuclei, were not significant. However, between post exposure and scattered radiation, all cytotoxic and genotoxic anomalies were insignificant. Conclusion: CBCT induces significant cytotoxic effects in oral mucosa cells, such as increased pyknosis, karyolysis, and karyorrhexis, but does not cause significant genotoxic damage. Scattered radiation also contributes to cytotoxic effects, though to a lesser extent than direct exposure. The radiation dose from CBCT, at lower levels, affects both the exposure site and the contralateral buccal mucosa equally, indicating that higher doses could potentially lead to greater cellular damage. Considering the established link between cytotoxicity and carcinogenesis, it is imperative to use CBCT with careful deliberation, ensuring adherence to the ALARA (As Low As Reasonably Achievable) principle to effectively mitigate potential risks.